Protecting the Planet or Destroying the Universe? Understanding Reactions to Space Mining - Hornsey, Matthew J.; Fielding, Kelly S.; Harris, Emily A.; Bain, Paul G.; Grice, Tim; Chapman, Cassandra M. (Sustainability, 2022)
There is currently a surge in interest from both private and government sectors in developing technology for mining asteroids and the moon (“space mining”). One of the key benefits highlighted by advocates of space mining is that it minimizes the usual problems associated with mining on earth in terms of pollution, environmental degradation, and encroachment on human habitats. Two studies—one conducted on a 27-nation sample (N = 4819), the other conducted in the U.S. (N = 607)—provide the first test of the assumed (but never studied) notion that space mining is more palatable to the public than terrestrial mining. Both studies indicate broad support for asteroid mining: levels of support were reliably above the mid-point, and much greater than for other forms of frontier mining such as mining the ocean floor, mining Antarctica, mining the Alaskan tundra, and lunar mining. Unlike terrestrial mining, community attitudes toward mining asteroids were largely non-ideological; support was not correlated with perceptions of ecological fragility, political ideology, or individualistic/hierarchical worldviews. In summary, the current studies suggest that mining companies have a “social license to operate” for mining asteroids, but less so for lunar mining.